A ∼28-kyr Continuous Lacustrine Paleoseismic Record of the Intraplate, Slow-Slipping Fuyun Fault in Northwest China - Fan, Jiawei; Xu, Hongyan; Shi, Wei; Guo, Qiaoqiao; Zhang, Siqi; Wei, Xiaotong; Cai, Minggang; Huang, Shuaitang; Wang, Jiangyong; Xiao, Jule (Frontiers in Earth Science, 2022)
The Fuyun Fault is a typical intraplate, slow-slipping fault, but has been repeatedly ruptured by surface wave magnitude (Ms) ≥ 8.0 earthquakes. The 11 August 1931 Ms 8.0 Fuyun earthquake resulted in more than 10,000 casualties in the sparsely populated Fuyun area. Cosmogenic 10Be dating of offset landforms produced by prehistoric Ms ≥ 8.0 earthquakes yields an average recurrence interval of 9700 yr, much longer than previously estimated 2000–4500 yr, clouding our understanding of the timing and recurrence behavior of past earthquakes originating from the Fuyun Fault. Reflection seismic data reveal widely distributed subaquatic faults in Yileimu Lake, implying extreme sensitivity of the lake sediments to paleoearthquakes originating from the Fuyun Fault. The mass-wasting deposits with underlying soft-sediment deformation structures (SSDS) in an 890-cm long sediment core from Yileimu Lake indicate 6 siliciclastic-enriched sandy sediment fluxes from earthquake-triggered landslides of granitic rocks, and independent SSDS record 3 additional earthquake-induced in situ deformations. Turbidite-like deposits with sorting indices > 3 and Si contents > 700 counts per second (cps) are comparable to those of the seismic mass-wasting deposits, and are thus interpreted as seismites from earthquake-induced subaquatic slumps or slope failures. Seismic intensity calculation results, combined with historical seismic data, provide potential magnitudes of Ms ≥ 8.0, Ms ≥ 7.0, and Ms ≥ 5.5 for the earthquake-triggered mass-wasting deposits, SSDS, and turbidite-like seismites, respectively, in Yileimu Lake. Radiocarbon dating and stratigraphic correlations constrain the timing of these past earthquakes to 28 cal kyr BP. This unique, long lacustrine paleoseismic record suggests a weakly periodic pattern with an average recurrence interval of 5303 yr for potential Ms ≥ 8.0 earthquakes, and reveals an unprecedented high frequency of potential Ms ≥ 7.0 earthquakes originating from the Fuyun Fault in the last 5 kyr, demonstrating the urgent need for an improved assessment of seismic hazards and risks in the Fuyun Fault zone.